2020
DOI: 10.22541/au.159242029.92154689
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of the Atomic Number of Alkali Atom and Pore Size of Graphyne on the Second Order Nonlinear Optical Response of Superalkali Salts of Graphynes OM3+@GYs– (M = Li, Na, and K)

Abstract: Based on the combination of novel carbon material graphynes (GYs) and superalkalis (OM 3), a class of graphyne superalkali complexes, OM 3 + @(GY/GDY/GTY)-(M = Li, Na, and K), have been designed and investigated by density functional theory method. Computational results reveal that these complexes with high stability can be regarded as novel superalkali salts of graphynes due to electron transfer from OM 3 to GYs. For second order nonlinear optical response, these superalkali salts exhibit large first hyperpol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…The total dipole moment (μ 0 ), static mean polarizability (α 0 ), and mean first hyperpolarizability (β 0 ) are given by where The projection of β on the dipole moment vector can be obtained as The static α 0 and β 0 values were analyzed using analytical derivatives of the system energy (coupled-perturbed Kohn–Sham method) at the CAM-B3LYP/6-31+G­(d) level of theory. The combination of CAM-B3LYP functional and 6-31+G­(d) basis set can provide a qualitative trend to extract the valuable NLO prediction for various complexes. , The time-dependent density functional theory (TD-DFT) is a common method for calculating the properties of excited states due to its efficiency and accuracy. , Hence, the transition energy (Δ E ) and oscillator strength ( f 0 ) were evaluated by employing the TD-CAM-B3LYP functional with the 6-31+G­(d) basis set.…”
Section: Computational Detailsmentioning
confidence: 99%
See 2 more Smart Citations
“…The total dipole moment (μ 0 ), static mean polarizability (α 0 ), and mean first hyperpolarizability (β 0 ) are given by where The projection of β on the dipole moment vector can be obtained as The static α 0 and β 0 values were analyzed using analytical derivatives of the system energy (coupled-perturbed Kohn–Sham method) at the CAM-B3LYP/6-31+G­(d) level of theory. The combination of CAM-B3LYP functional and 6-31+G­(d) basis set can provide a qualitative trend to extract the valuable NLO prediction for various complexes. , The time-dependent density functional theory (TD-DFT) is a common method for calculating the properties of excited states due to its efficiency and accuracy. , Hence, the transition energy (Δ E ) and oscillator strength ( f 0 ) were evaluated by employing the TD-CAM-B3LYP functional with the 6-31+G­(d) basis set.…”
Section: Computational Detailsmentioning
confidence: 99%
“…The tunable direct band gap of GDY is about 0.46 eV, , which reveals its great potential in photonic fields. In recent years, great efforts have been devoted to exploring the NLO properties of graphyne/graphdiyne-based compounds . Especially, the graphyne structure is very advisable for the design of novel NLO materials because it has a delocalized π-conjugated surface that can accommodate dopants to enhance the NLO response. Li et al ,, introduced (super)­alkali metals into GDY, confirming that the (super)­alkali metal doping effect significantly improved the first hyperpolarizability (β 0 ) of GDY. We found that the β 0 value of the OM 3 + @GYs – (M = Li, Na, and K) depends on the atomic number of the alkali atom and the pore size of GY .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation